In vitro and in vivo activity of a palladacycle complex on Leishmania (Leishmania) amazonensis. - Carolina de Siqueira Paladi; Isabella Aparecida Salerno Pimentel; Simone Katz; Rodrigo L O R Cunha; Wagner Alves de Souza Judice; Antonio C F Caires; Clara Lúcia Barbiéri (PLoS Neglected Tropical Diseases, 2012)
BACKGROUND: Antitumor cyclopalladated complexes with low toxicity to laboratory animals have shown leishmanicidal effect. These findings stimulated us to test the leishmanicidal property of one palladacycle compound called DPPE 1.2 on Leishmania (Leishmania) amazonensis, an agent of simple and diffuse forms of cutaneous leishmaniasis in the Amazon region, Brazil. METHODOLOGY/PRINCIPAL FINDINGS: Promastigotes of L. (L.) amazonensis and infected bone marrow-derived macrophages were treated with different concentrations of DPPE 1.2. In in vivo assays foot lesions of L. (L.) amazonensis-infected BALB/c mice were injected subcutaneously with DPPE 1.2 and control animals received either Glucantime or PBS. The effect of DPPE 1.2 on cathepsin B activity of L. (L.) amazonensis amastigotes was assayed spectrofluorometrically by use of fluorogenic substrates. The main findings were: 1) axenic L. (L.) amazonensis promastigotes were destroyed by nanomolar concentrations of DPPE 1.2 (IC50 = 2.13 nM); 2) intracellular parasites were killed by DPPE 1.2 (IC50 = 128.35 nM), and the drug displayed 10-fold less toxicity to macrophages (CC50 = 1,267 nM); 3) one month after intralesional injection of DPPE 1.2 infected BALB/c mice showed a significant decrease of foot lesion size and a reduction of 97% of parasite burdens when compared to controls that received PBS; 4) DPPE 1.2 inhibited the cysteine protease activity of L. (L.) amazonensis amastigotes and more significantly the cathepsin B activity. CONCLUSIONS/SIGNIFICANCE: The present results demonstrated that DPPE 1.2 can destroy L. (L.) amazonensis in vitro and in vivo at concentrations that are non toxic to the host. We believe these findings support the potential use of DPPE 1.2 as an alternative choice for the chemotherapy of leishmaniasis.